2009
DOI: 10.1007/s11250-009-9399-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bovine cysticercosis in slaughtered cattle in Iran

Abstract: Bovine cysticercosis is an important food safety issue and can cause economic loss. A cross sectional study on Taenia saginata cysticercosis was carried out in slaughtered cattle in Iran in order to determine the infection rate during a three-years period, from 2005 to 2007. A total of 4,534,105 cattle were examined by routine meat inspection. The results showed that 11,410 cattle (0.25 %) were infected with Cysticercus bovis; among those 1,041 carcasses (0.02%) were condemned. In such carcasses the metacestod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
4
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 1 publication
3
15
4
12
Order By: Relevance
“…A similarity can be observed comparing the prevalence assessed in this study with those reported in other countries, such as Iran (0·25%) (Khaniki et al 2010), Chile (0·58%) (Faustina et al 2012) and European countries (<1%) (Laranjo-González et al 2016). The no-detection of bovine cysticercosis in animals slaughtered from two municipalities does not mean a real absence of this disease at these areas due to the low sensitivity of the ongoing model of meat inspection and the practice of slaughter without inspection (illegal), which remains occurring in this state (Lopes et al 2011).…”
Section: Discussionsupporting
confidence: 86%
“…A similarity can be observed comparing the prevalence assessed in this study with those reported in other countries, such as Iran (0·25%) (Khaniki et al 2010), Chile (0·58%) (Faustina et al 2012) and European countries (<1%) (Laranjo-González et al 2016). The no-detection of bovine cysticercosis in animals slaughtered from two municipalities does not mean a real absence of this disease at these areas due to the low sensitivity of the ongoing model of meat inspection and the practice of slaughter without inspection (illegal), which remains occurring in this state (Lopes et al 2011).…”
Section: Discussionsupporting
confidence: 86%
“…However, it is important to mention that only a few EU countries submit reports to the World Animal Health Organisation, thus the statistical data are not representative enough to draw any kind of conclusions about the distribution of this disease in Europe. It is well known that teniasis and cysticercosis are the most important problem of the public health in African .... and Asian countries (Kebede, 2008;Qadeer, 2008;Kebede et al, 2009;Rabi'u & Jegede, 2010;Khaniki et al, 2010), but the risk could be present elsewhere (Rudohradská et al, 2012). The available data on the presence of C. bovis in cattle determined by traditional meat inspection in our region (Western Balkans) indicate a diversity in prevalence (from 0.43 % to 22.4 %), which largely depends on the number of examined animals, their age, origin, the breeding manner, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is distributed throughout Iran, especially in rural areas (1,3). This disease is a relatively innocuous parasitic zoonosis caused by the larvae of T. saginata, commonly known as beef tapeworm.…”
Section: Introductionmentioning
confidence: 99%
“…Although predilection sites are commonly examined in areas where regular post-mortem screening is performed, such measures are not adequately sensitive, especially for the detection of light infections (11,12). Some researches on bovine cysticercosis have previously been conducted in Iran (1,3). Tabriz, the capital of East Azerbaijan Province, Northwest Iran, is one of the important areas for training domestic animals.…”
Section: Introductionmentioning
confidence: 99%